Phytochemistry, metabolites quantification and antioxidant activity of Calotropis procera (Ait.) and Ficus umbellata (Vahl.), plants traditionally used against hemorrhoids in Benin. - YOMAKOU B. Georges, G. René; GLINMA, BIENVENU; ASSOGBA, M. Fidèle; YAYI-LADEKAN, Eléonore; GBENOU, Joachim D. (My University, 2021)
Hemorrhoidal disease is a very present ailment that manifests itself in our societies and sometimes leads to cases of surgery. The traditional treatment in Benin is based on the use of medicinal plants. Calotropis procera (Ait.) and Ficus umbellata (Vahl.) are two plants well known in West Africa, precisely in Benin. They are among the most used plants in traditional medicine. Their different preparations are mainly used against several sickness as tuberculosis, uterine myomas and fibroids, malaria, hemorrhoids... These uses of the two plants were reported in the cities of Porto-Novo and Abomey-Calavi. In order to verify the effects of these plants on hemorrhoids, preliminary studies were carried out. Phytochemical studies of fresh leaves and leaf powders revealed, among other things, the presence of total polyphenols, flavonoids, tannins and traces of essential oil. The different assays showed that F. umbellata is richer in total polyphenols (377.97 mg.EqAG/g extract), flavonoids (10.97 mg.EqRUT/g extract) and tannins (33.13 mg.EqPYR/g extract) than C. procera. The extract without potash of C. procera is richer in phenolic compounds (139.107 mg.EqAG/g extract) than which with potash (63.54 mg.EqAG/g extract). Antioxidant activity was measured for all extracts, and the aqueous extract of F. umbellata exhibited the highest activity (14.24 μg / mL).
Keywords: Medicinal plants; Calotropis procera; Ficus umbellata; Hemorrhoids; Treatment